A Review on Ã¢â‚¬Å“Churg-Strauss VasculitisÃ¢â‚¬Â - Gnaneshwari, R.K. Sharma, K. Kinja*, S. Rohit, A. Mandloi, D. (Recent Research in Science and Technology, 2011)
Churg-Strauss syndrome (CSS) is a systemic disorder characterized by asthma, transient pulmonary infiltrates, hypereosinophilia, and systemic vasculitis. Eosinophilicvasculitis may involve multiple organ systems, including the lungs, heart, skin, gastrointestinal tract and nervous system. Thus allergy and angiitis are the two hallmarks of CSS. Conditions in the differential diagnosis of CSS include Wegener's granulomatosis (WG), drug reactions, bronchocentricgranulomatosis, eosinophilic granuloma, fungal and parasitic infections, and malignancy. Onset typically occurs in patients aged from 15 to 70 years.On presentation, patients often have pulmonary infiltrates on chest x-ray, but they may also have sinusitis, neuropathy, constitutional symptoms, or gastrointestinal or cardiac manifestations. It is important to establish a tissue diagnosis by biopsy and exclude other diseases in the differential diagnosis of CSS because treatment differs significantly from that of other eosinophilic lung diseases. Untreated, CSS may have a dire prognosis, but treatment with corticosteroids or cytotoxic agents, or both,usually results in clinical remission. Although the exact etiology of CSS is unknown, this syndrome is likely believed to represent an autoimmune process because of the prominence of allergic features and the presence of immune complexes, heightened T-cell immunity and altered humoral immunity, as shown by elevated immunoglobulin (Ig) E and rheumatoid factor. Treatment consists of glucocorticoid (GC)-monotherapy, data on outcome and affectivity is lacking on other immunosuppressive regimens such as cyclophosphamide (CP) or GC plus CP. Treatment with INF-alpha has been effective in patients refractory to GC plus CP.